Reproductive health status of women in the matrilineal tribes of Meghalaya: a field-based quantitative study - Mavelil, Sunny Joseph; Srivastava, Subhash Chandra (International Journal Of Community Medicine And Public Health, 2019)
Background: Reproductive health of the tribal women in India is less studied and the present study attempts to fill the gap by understanding the reproductive health of women in the matrilineal tribes in Meghalaya. The objective of the study was to study the reproductive health status of tribal women. Methods: A field-based quantitative study was conducted among randomly chosen 900 tribal women in their reproductive age from the 142 villages selected randomly across 15 PHCs functional in five districts. We used a semi-structured validated questionnaire consisting of the socio-demographic profile, reproductive health status, blood pressure and haemoglobin level. Results: Median age of the 900 respondents was 28.9 years, 83% had primary education and 82% got married between 13-18 years. Over 96% lived with their spouse, and 80% had a monthly income ≤Rs. 5000. Their mean age at menarche was 14.3 years, 10% reported menstrual issues: stomach ache, back pain and vomiting. Though 58% planned their pregnancy, 77% had their first pregnancy before 18 years, and 10.3% of respondents had three deliveries within a four-year period. 76% had poor self-rated health, 83% had abnormal blood pressure and 95% reported anaemia. Out of 81 deaths, 69% were infants and 33.3% did not avail medical service from PHC. Conclusions: Reproductive health risks, anaemia and abnormal blood pressure were found among women in Garo tribes. Mitigating the ill effects of reproductive health issues through indigenous interventions as part of the NRHM program is needed.